Income Distribution and Social Expenditure in Brazil - Clements, Benedict (Washington, D.C. : International Monetary Fund, 1997)
This paper examines trends in income distribution in Brazil and the determinants of income inequality, including social expenditure. While recent data reveal reduced income inequality since the Real Plan of July 1994, the distribution of income is still among the most unequal in the world. Among the most important determinants of income inequality in Brazil is extreme disparity in educational attainment levels. Public expenditures on education, health, and social insurance have tended to exacerbate income inequality. A number of options for improving the equity and efficiency of Brazilian social expenditure merit further examination.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet